Fatores que influenciam a probabilidade das práticas de disclosure de informações financeiras das empresas - Lima, Samuel Lyncon Leandro de (2018)
Voluntary disclosure of financial information consists of a theme with a fundamental role in Accounting, and in this sense, many authors have discussed for some decades, mainly with the studies of Verrecchia (1983) and Dye (1985). Among the aspects worked on the issue of voluntary disclosure is the reduction of informational asymmetry. From this perspective, considering the importance of maximizing transparency, arising from the practice of voluntary disclosure, sought to perform analyzes with eight logit regression models, based on Brazilians non-financial companies listed on the Brazil Bolsa Balcão S.A., in 2016. The research differential was to distinguish the respective dependent variables with the aid of a quality metric for the comparison amongst published information of the companies in question. We have Murcia’s study (2009) as a reference to establish which variables, in principle, more explain the willingness of companies to publish voluntarily information. Therefore, we tried to answer the following research question: "What is the probability of the explanatory variables selected influence the practices of voluntary disclosure in Brazilian non-financial companies listed on the Brazil Bolsa Balcão S.A, in 2016?”. Thereby, we have carried out the analysis of the data in two stages. The first one consisted of an in-depth survey on the content of the publications carried out by the sample companies, aiming to qualify, comparatively, the information evidenced by the companies, under the parameter of a metric constructed contemplating the quality of the information. This first stage of the analysis was performed in addition to identifying the level of voluntary disclosure of companies, by segment of activity and economic sector for the construction of dependent variables. Therefore, in the second stage of the data analysis, we worked with the logit regression models proposed in the research, with the objective of estimating the probability of practicing the voluntary disclosure of financial information. As the main results, when verified the data presented by the estimated regression models, it was found that the coefficients associated with corporate governance and audit have a positive influence expressive on a probability of disclosure of information, so coefficients of the first variable were statistically significant in the integral of the estimated models. In addition, regarding the results presented by the coefficients associated with the explanatory variables related to the economic and financial performance of the companies, none presented statistical significance. Finally, although the theme of voluntary disclosure has been, extensively, discussed in the literature, it still has gaps to be explored that would contribute to the advancement of these discussions.